A quantitative histological study of testicular and epididymal development in Boran and Boran X Friesian bulls in Ethiopia - Tegegne, Azage; Entwistle, K.W.; Mukasa-Mugerwa, E. (1991)
Reports the results of a study carried out to determine the pattern of testicular and epididymal development in 42 Boran and 49 Boran X Friesian bulls aged between 6 and 23 months, by using quantitative histological techniques.